Atypical hemolytic uremic syndrome and eculizumab therapy in children - Seong Heon Kim; Hye Young Kim; Su Young Kim (Korean Pediatric Society, 2018)
Hemolytic uremic syndrome (HUS) is often encountered in children with acute kidney injury. Besides the well-known shiga toxin-producing Escherichia coli-associated HUS, atypical HUS (aHUS) caused by genetic complement dysregulation has been studied recently. aHUS is a rare, chronic, and devastating disorder that progressively damages systemic organs, resulting in stroke, end-stage renal disease, and death. The traditional treatment for aHUS is mainly plasmapheresis or plasma infusion; however, many children with aHUS will progress to chronic kidney disease despite plasma therapy. Eculizumab is a newly developed biologic that blocks the terminal complement pathway and has been successfully used in the treatment of aHUS. Currently, several guidelines for aHUS, including the Korean guideline, recommend eculizumab as the first-line therapy in children with aHUS. Moreover, life-long eculizumab therapy is generally recommended. Further studies on discontinuation of eculizumab are needed.